MARCH OF ARAB TROOPS TO FERGANA DURING THE REIGN OF THE GOVERNOR OF KHUROSAN NASR IBN SAYYOR (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
In the article, for the first time, based on an analysis of historical sources and literature, political processes in the Fergana Valley during the Arab invasion are investigated.